Psycho-social Perception of Indoor Air Quality in Students Dormitory: A Preliminary Assessment - Sani Khalil , Ibrahim; Alhaji Mohammed, Mohammed (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Campus housing acts as an essential facility in smoothing students' lives and speeding up the learning process, thus achieving the overall university mission. This study evaluates the psychosocial perception of satisfaction with the indoor environmental quality in student housing at King Fahd University of Petroleum and Minerals (KFUPM), Dhahran, Saudi Arabia. The study used a questionnaire survey for data collection and simple descriptive statistics for data analysis. The results indicate that the respondents are satisfied with the room temperature during summer (56%), quality of air inside the room, control of natural ventilation using window openings (42%) and level of smell inside their rooms (88%). However, the respondents are dissatisfied with room temperature during winter (48%), the overall perception of thermal environment in the building (48%), mechanical ventilation control (72%), overall perception of the indoor air quality (60%) and smell throughout the corridors (54%). The outcome of this study is essential information for facility managers, building designers and owners. The result will also benefit decision-makers to formulate policies.